Total Quality Management (TQM); A Means of Better Work Output in Nigerian Manufacturing Industries - Olusegun Ajayi, Paul (British Journal of Marketing Studies, 2021)
The study inquiries into the role total quality management plays in facilitate an organization output. It suggests that the management of an organization is determined by TQM and its application is complex and gives an assurance of good products and services. The study revealed that human, material resources and busines processes ensure complete customer satisfaction at every stage, internally and externally. The combination of TQM and effective leadership, results in an organisation doing the right things at the right time. For methodological purpose, the study employed expository and content analytics approach to extrapolate the relationship between TQM and the work output in manufacturing industries. It concludes that total quality management and service delivery in manufacturing industries in Nigeria shares common attributes and would be able to contribute successfully to the achievement of the organization aims.